Observational study of mental health in asthmatic women during the prenatal and postnatal periods. (2nd August 2020) - Whalen, Olivia M.; Campbell, Linda E.; Murphy, Vanessa E.; Lane, Alison E.; Gibson, Peter G.; Mattes, Joerg; Collison, Adam; Mallise, Carly A.; Woolard, Alix; Karayanidis, Frini
Abstract: Objective: We aimed to examine the prevalence and severity of psychological distress of women with asthma in both the prenatal and postnatal periods, and to determine whether asthmatic women with and without mental health problems differ in self-management, medications knowledge, and asthma symptoms. Methods : We assessed spirometry performance and asthma symptoms in 120 women (mean age 29.8 years) before 23 weeks gestation, as part of the Breathing for Life Trial (Trial ID: ACTRN12613000202763). Prenatal depression data was obtained from medical records. At 6 weeks postpartum, we assessed general health, self-reported asthma control, depression symptoms (with the Edinburgh Postnatal Depression Scale) and adaptive functioning (with the Achenbach System of Empirically Based Assessment scales). Results : Twenty percent of our sample reported having a current mental health diagnosis, 14% reported currently receiving mental health care, while 47% reported having received mental health care in the past (and may/may not have received a diagnosis). The sample scored high on the Aggressive Behavior, Avoidant Personality, and Attention Deficit/Hyperactivity scales. Poorer self-reported postnatal asthma control was strongly correlated with elevated somatic complaints, externalizing problems, antisocial personality problems, and greater withdrawal. Prenatal spirometry or asthma severity and control were largely not associated with measures of psychopathology. Conclusions : These findings indicate that pregnant women with asthma frequently report issues with psychopathology during the prenatal and postnatal periods, and that the subjective perception of asthma control may be more related to psychopathology than objective asthma measures. However, due to sample bias, these findings are likely to be understated.